9x-5.4=-2.7x+42

Simple and best practice solution for 9x-5.4=-2.7x+42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-5.4=-2.7x+42 equation:


Simplifying
9x + -5.4 = -2.7x + 42

Reorder the terms:
-5.4 + 9x = -2.7x + 42

Reorder the terms:
-5.4 + 9x = 42 + -2.7x

Solving
-5.4 + 9x = 42 + -2.7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2.7x' to each side of the equation.
-5.4 + 9x + 2.7x = 42 + -2.7x + 2.7x

Combine like terms: 9x + 2.7x = 11.7x
-5.4 + 11.7x = 42 + -2.7x + 2.7x

Combine like terms: -2.7x + 2.7x = 0.0
-5.4 + 11.7x = 42 + 0.0
-5.4 + 11.7x = 42

Add '5.4' to each side of the equation.
-5.4 + 5.4 + 11.7x = 42 + 5.4

Combine like terms: -5.4 + 5.4 = 0.0
0.0 + 11.7x = 42 + 5.4
11.7x = 42 + 5.4

Combine like terms: 42 + 5.4 = 47.4
11.7x = 47.4

Divide each side by '11.7'.
x = 4.051282051

Simplifying
x = 4.051282051

See similar equations:

| (1/3h)(3h) | | y=.10x+21.59 | | 1/2x+16=0 | | b=108(0.9) | | y^3-y^2=12 | | 1/8(x-48)=7/8 | | 6m^2+13m-15=0 | | x+x+0.11+x+0.11+0.18=8.44 | | 5y^2+23y+12=0 | | -12+3x=-8+x | | 4u^2-u-60=0 | | 18x+12=9x+34 | | 3+6x=6+3x | | 3x-2+2x+3x-2+2x= | | -0.17-(14.6)=g | | -3+4x=7-x | | 3(n-7)=2n-8 | | u^2+12u+36=0 | | 7+2x=-3+4x | | -3x+8=x-12 | | 2w^4x^4-32w^4= | | 2x+1/4+9/4 | | y=7x+37 | | 16u^2-u^2v^4= | | 2x-8(0)=24 | | 2(0)-8y=24 | | 0.2+6.51+2.03=a | | -8y=2 | | 3y=9x-24 | | -12.5+20.13=W | | x+x+0.56+x+0.56+1.08=10.51 | | c=9.8+(-2.5) |

Equations solver categories